79.3k views
5 votes
Solve for x:-

\tt 4x-3\left(2x+1\right)=4\left(x+2\right)+1

User Thanos
by
5.9k points

2 Answers

3 votes
4x - 3(2x+1) = 4(x+2) + 1
4x - 6x - 3 = 4x + 8 + 1
-2x - 3 = 4x + 9
-3 = 6x + 9
-12 = 6x
x = -2
User Retgoat
by
5.5k points
2 votes

Answer:

–2 is the correct Answer

Explanation:


\: 4x - 3(2x + 1) = 4(x + 2) + 1 \\ ⇒4x - 6x - 3 = 4x + 8 + 1 \: \: \: \: \: \: \: \: \: \: \: \: \\ ⇒4x - 6x - 4x =9 + 3 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\\ ⇒ - 6x = 12 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ ⇒x = - (12)/(6) = - 2 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \:

User BoobyTrap
by
5.7k points